2010
DOI: 10.2516/ogst/2009078
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Penalty Comparison for (Electrically) Heated Catalyst Technology

Abstract: Résumé -Comparaison de l'augmentation de consommation de carburant pour la technologie de catalyseurs chauffés à l'électricité -L'efficacité de conversion des catalyseurs est principalement définie par la gamme de température dans laquelle ils fonctionnent. Un retard du point d'allumage a traditionnellement été utilisé pour réduire le temps d'amorçage du catalyseur. Ceci est cependant associé à une augmentation de la consommation de carburant. Avec l'électrification des véhicules, la possibilité de chauffage é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The effect of shortening the warming-up phase of the catalytic converter to the operating temperature by increasing the temperature of exhaust gases internally in the engine is weakened by intensified heat exchange with the walls of the additional expansion cylinders and elements of the engine exhaust system. In order to substantially shorten the warming up time of a catalytic converter, the use of an external, hardware method, such as the use of electric heating of the reactor support, should be considered and balanced [25,42]. Another idea is the relocation of the catalytic converter upstream from the turbine.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of shortening the warming-up phase of the catalytic converter to the operating temperature by increasing the temperature of exhaust gases internally in the engine is weakened by intensified heat exchange with the walls of the additional expansion cylinders and elements of the engine exhaust system. In order to substantially shorten the warming up time of a catalytic converter, the use of an external, hardware method, such as the use of electric heating of the reactor support, should be considered and balanced [25,42]. Another idea is the relocation of the catalytic converter upstream from the turbine.…”
Section: Discussionmentioning
confidence: 99%
“…The TWC temperature must exceed a certain thresholdcommonly referred to as the light-off temperature-before the catalytic oxidation and reduction reactions required to convert criteria pollutants to nitrogen, carbon dioxide, and water become active. The majority of the criteria pollutants emitted by modern vehicles equipped with SI engines are released during the cold-start period immediately after the engine is turned on (Kessels et al 2010).…”
Section: Catalyst Warmupmentioning
confidence: 99%
“…Three-way catalyst heating typically is achieved through injection of extra fuel and delayed spark timing, which effectively dumps extra heat into the exhaust system to rapidly increase the temperature of the TWC. Although such strategies are necessary to meet emissions regulations, they also incur a fuel penalty because the engine is not operating under optimal conditions for high efficiency during the cold-start process (Kessels et al 2010. The magnitude of the fuel penalty depends on how long it takes for the catalyst to achieve light-off: increased light-off temperatures require more time under the cold-start strategy, resulting in a larger fuel penalty.…”
Section: Catalyst Warmupmentioning
confidence: 99%
See 1 more Smart Citation
“…Richer fuel/air mixtures, variable valve timing, retarded ignition, heat storage devices, and electrically heated catalysts (EHCs) have been implemented for the thermal management of catalytic converters, with a light‐off time reduction from 20 seconds to 300 seconds depending on the system. Kessels et al investigated the effect of ignition delay on the catalyst light‐off time and fuel consumption, and concluded that the fuel penalty was approximately 50% for decreasing the light‐off time from 105 seconds to 19 seconds. Lee et al applied enriched air/fuel mixture and secondary air injection to a naturally aspired engine.…”
Section: Introductionmentioning
confidence: 99%